Assessment of Ventilation and Air Cleaning System Design Approaches for Nuclear Safety Requirement during Accidental Conditions in Nuclear Fuel Cycle Facilities (Journal of Nuclear Technology in Applied Science, 2018)
Safe operation of the nuclear and radiological facilities requires coners and the environment according to ALARA principle. Most nuclear paper provides and evaluates four different design concepts or safety per-formance approaches of the ventilation and air cleaning system (VACS)that can be used to achieve safety and adequate protection in nuclearventilation and air cleaning system protection and a discussion of se-and their engineered and administrative safety features.Finally a conclusion of the selection of the best design concept is recom-mended.Brassica Oleracea L.Var Italica) Powder Journal of NUCLEAR Technology in Applied Science ISSN 2314-8209 e-ISSN 2314-8217Brassica Oleracea L.Var Italica) Powder Journal ofNUCLEARTechnology in Applied Science ISSN 2314-8209 e-ISSN 2314-8217ji/Jers, Fire andfinement of radioactive and toxic materials involved behind suitable barriers which provide sufficient shielding. This is to minimize the internal and external radiation hazards at prescribed limits to protect plant work facilities can expect to have at least one fire accident during its operating life. Such fire events are energized with the potential to damage confinement barriers and transport radioactive materials out of the building. This fuel cycle facilities during fire and accidental criticality conditions. The work presents a summary of the recent international requirements for lected fire protection considerations in designing nuclear facilities.
Keywords: Ventilation and Air Cleaning System; radiological facilities; nuclearventilation